Biologically Active Nonribosomal Peptides. II. Nonribosomal Peptides of Various Biological Action - T. I. Orlova; V. G. Bulgakova; A. N. Polin (Антибиотики и Химиотерапия)
The second part of the review concerned with investigation of nonribosomal peptides.